(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Bao TQ, Viet LH, Hai NH, Tuan NT, Cuong LV. 2021. Population dynamics and regeneration of Shorea roxburghii, a threatened timber species in Southern region, Viet Nam. Biodiversitas 22: 5649-5656. Despite its wide distribution in South and Southeast Asia, Shorea roxburghii G. Don is classified as Vulnerable in the IUCN Red List of Threatened Species due to over-exploitation for its valuable timber. This study aims to investigate the population dynamics and regeneration of S. roxburghii in southeastern Vietnam, serving for conservation and sustainable development plan. Six plots of 2,500 m2 each (50 m × 50 m) were established at two forest conditions: i) forest with standing volume > 200 m3/ha (SV>200), and ii) < 200 m3/ha (SV<200); to investigate stems with diameter at breast height (DBH) ? 5 cm and that < 5 cm. Moisture (%), pHH2O of the topsoil and the occurrence of regenerating S. roxburghii were collected from 125 points in the study site. The results indicated that mean stem height, DBH, basal area, and aboveground biomass were significantly higher at the forest stand with SV>200 than that at the forest stand with SV<200 for the pool of all species. Similar higher figures were found in SV>200 for the pool of S. roxburghii compared to that in SV<200, except mean DBH, which was larger in SV<200. There were missing stems with DBH < 5 cm in SV<200, while it was numerous in SV>200 (1,313 stems/ha). DBH/stem distributions in both forest types had an inverted-J shape with a peak at 10-15 cm DBH for the pool of all species, while there was no clear pattern for the pool of S. roxburghii in both forest types. Regression analysis indicated that higher total crown area of stems ? 23 tall leads to higher S. roxburghii stems, while the higher total crown area of stems < 23 tall leads to fewer S. roxburghii stems with DBH < 5 cm. It is concluded that the total crown area of forest stand plays an important role in the sustainable regeneration of S. roxburghii. Silvicultural treatment should be applied to reduce stand density and crown area of stems < 23 m tall to enhance sunlight reaching the forest floor for germination, growth, and survival of S. roxburghii. The moisture of the topsoil ranging from 60 - 80% and the pHH2O ranging from 3.8 - 4.6 are suitable conditions for natural regeneration of S. roxburghii.